Fossil sardines from the Pisco Formation (Miocene), Peru: Taxonomy, taphonomy, and paleoecology - Carnevale, Giorgio (2026)
The Miocene sedimentary sequences of the Pisco Formation (Eastern Pisco Basin, southern Peru) are renowned for the abundance of fossil vertebrates that document the early evolution of the biotic communities of the Humboldt Current Ecosystem. Vertebrate remains are often exceptionally preserved, representing a variety of fishes, turtles, crocodiles, birds, and marine mammals. Here, we describe a new species of sardine, Sardinops humboldti n. sp., based on partially complete articulated skeletons from the Upper Miocene P2 sequence of the Pisco Formation. This new species is morphologically similar to the extant Indian-Pacific species S. sagax from which it differs by having larger parietals, a thick and much elongate supraoccipital crest, anterolateral processes of the sphenotics that protrude obliquely from the skull roof, posterior margins of the supraoccipital and epioccipitals forming a broad acute angle approaching 90°, and gently rounded ventral margin of the opercle. Taphonomic and paleoecological evidences suggest that S. humboldti n. sp. was probably very abundant in the Eastern Pisco Basin where it formed relatively small schools of large individuals that were uniform in size, representing the trophic nucleus of the diverse vertebrate communities. Paleobiogeographic implications are also discussed.